Chato's kitchen - Soto, Gary.; Guevara, Susan (New York, NY : PaperStar, 1997)
To get the "ratoncitos, " little mice, who have moved into the barrio to come to his house, Chato the cat prepares all kinds of good food: fajitas, frijoles, salsa, enchiladas, and more.
Keywords: Cats -- Fiction; Mice -- Fiction; Cats -- Juvenile fiction; Mice -- Juvenile fiction; Gatos -- Novela juvenil; Ratones -- Novela juvenil; Los Angeles (Calif.) -- Fiction; Los Angeles (Calif.) -- Juvenile fiction; Los Angeles (Calif.) -- Novela juvenil